(3JMaI GdYQhS hfRgI GdfahSs - (3GdJLGfj , eMeO Hf CMeO Hf eMeO, CHh YHO Gddg,J (B711 (3g` s
(3ChdgG (B:s
(3CeG HYO (B:(3aEf Gddg JYGdi Ndb GdEfSGf eLHhdG Ydi GdGaJbGQ , hWHYg ai CUd NdbJg Ydi GdGMJjGL Edi GdScf hGdGVWQGQ hdeG cGf GdJdPP HGdfSGA CYXe GddPGJ QCjfG Cf fLeY ef edM CNHGQgf , heSJXQa fhGOQgf hCTYGQgf s
(3BNQgG (B:s
(3abGd (B:(3GSCdhG ef YaGagG abjd dg (B: (3gi CYa GdfGS ,aCQSd EdjgG eGdG LRjdG hbGd (B: (3JSJYjf Hg Ydi LeGdgG hQhfb COHgG s
(3HChdgG YOI JedcGJ GbOegG SfI (B929(3g`s
(3cJH YdjgG JMaI GdYQhS heJYI GdfahSs
(3fSNI KGdKIs
(3fajSIs
(3hYdjgG ebGHdI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs